Implementation of the Government Internal Control System (SPIP) in Realizing Good Governance at the General Bureau of the Regional Secretariat of Central Papua Province - Sulistyorini Ariwibowo; Manuel A Todingbua; Naomi Patiung (Jurnal Indonesia Sosial Teknologi, 2025)
This research aims to analyze the implementation of the Government Internal Control System (SPIP) in realizing Good Governance at the General Bureau of the Regional Secretariat of Central Papua Province. The research employs a qualitative approach. The informants in this study comprise six employees from the General Bureau of the Regional Secretariat of Central Papua Province. The data analysis technique employed is qualitative descriptive analysis, which involves collecting, reducing, presenting, and drawing conclusions from the data. This study concludes that: 1) The implementation of the Government Internal Control System (SPIP) in the General Bureau of the Regional Secretariat of Central Papua Province is carried out by establishing clear policies and procedures for internal control, providing routine training for employees, forming a special team to supervise and evaluate the implementation of SPIP periodically,  implementing information technology, and involving external oversight. 2) The obstacles to implementing SPIP in the General Bureau of the Regional Secretariat of Central Papua Province include a lack of understanding and awareness among employees, limited human resources, inadequate information technology infrastructure, resistance to change, and difficulties in integrating SPIP. 3) Implementing the Government Internal Control System (SPIP) at the Central Papua Province Regional Secretariat has benefits in creating public trust in the government. With an open and accountable system, the public feels more involved in the government process, encouraging increased public participation and supporting the creation of Good Governance. SPIP is crucial in ensuring transparent, accountable, and trustworthy financial management.